2020
DOI: 10.1016/j.neuron.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

How Can Hearing Loss Cause Dementia?

Abstract: Epidemiological studies identify midlife hearing loss as an independent risk factor for dementia, estimated to account for 9% of cases. We evaluate candidate brain bases for this relationship. These bases include a common pathology affecting the ascending auditory pathway and multimodal cortex, depletion of cognitive reserve due to an impoverished listening environment, and the occupation of cognitive resources when listening in difficult conditions. We also put forward an alternate mechanism, drawing on new i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
220
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(242 citation statements)
references
References 143 publications
(161 reference statements)
5
220
0
4
Order By: Relevance
“…Hearing loss (HL) is one of the leading causes of disability in older adults and is commonly associated with increased rates of depression, social isolation, and risk of cognitive decline (Livingston et al 2020;Mick, Kawachi, and Lin 2014;Strawbridge et al 2000). The mechanism of the hearing-cognitive decline relationship has yet to be elucidated, but one theory is an indirect association through the loneliness/social isolation pathway (Griffiths et al 2020). People with HL are more likely to report feelings of loneliness and social isolation (Huang et al 2020;Mick, Kawachi, and Lin 2014;Shukla et al 2020) and these factors have been shown to increase the risk of developing dementia (Fratiglioni et al 2000;Wilson et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss (HL) is one of the leading causes of disability in older adults and is commonly associated with increased rates of depression, social isolation, and risk of cognitive decline (Livingston et al 2020;Mick, Kawachi, and Lin 2014;Strawbridge et al 2000). The mechanism of the hearing-cognitive decline relationship has yet to be elucidated, but one theory is an indirect association through the loneliness/social isolation pathway (Griffiths et al 2020). People with HL are more likely to report feelings of loneliness and social isolation (Huang et al 2020;Mick, Kawachi, and Lin 2014;Shukla et al 2020) and these factors have been shown to increase the risk of developing dementia (Fratiglioni et al 2000;Wilson et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Aging is associated with a decline in processing auditory temporal features (Gordon-Salant and Fitzgibbons, 1999) and speech intelligibility, particularly in the presence of background sounds (Gordon-Salant, 2006). In addition to peripheral hearing loss (presbycusis) (Frisina and Frisina, 1997) and cognitive decline (Wayne and Johnsrude, 2015; Griffiths et al, 2020), evidence increasingly suggests that poorer speech intelligibility in older individuals may be related to changes in how the cerebral cortex responds to amplitude envelopes (Millman et al, 2017; Goossens et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The potential mechanisms underlying the association between ARHL and cognitive decline, particularly increased risk of dementia [ 19 ], remain unclear. Although Füllgrabe et al suggested that audibility and processing effort can bias the cognitive test performance toward cognitive decline [ 24 ], Griffiths et al proposed a mechanism linking auditory cognitive processing in the medial temporal lobe and dementia pathology [ 25 ]. Previously, Wayne and Johnsrude summarized the four directional hypotheses for the relationship between ARHL and cognitive decline, namely the cognitive load on perception hypothesis, sensory deprivation hypothesis, information degradation hypothesis, and common cause hypothesis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%